Blue-light perovskite nanorod material, light-emitting diode and preparation method of blue-light perovskite nanorod material

By ultrasonic synthesis and ligand exchange modification of FAPbBr3 nanorods at room temperature using a cell crusher, the problems of synthesis of perovskite nanorods and lead ion defects at lower temperatures were solved, and the preparation of high PLQY and stable perovskite nanorods was achieved, which significantly improved the performance of the light emitting diode.

CN119823754APending Publication Date: 2025-04-15SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510009467.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-20
Filing Date
2025-01-02
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

It is difficult to synthesize high PLQY and stable perovskite nanorods at lower temperatures in the prior art, and the perovskite nanorods have many lead ion defects, which affects their conductivity and photoelectric properties.

Method used

The reactant solutions of lead acetate trihydrate, formamidine acetate, oleamine bromine and oleic acid were synthesized at room temperature by ultrasonication using a cell crusher to prepare FAPbBr3 nanorods, and the surface of the nanorods was modified by a ligand exchange strategy to reduce lead ion defects and improve conductivity.

Benefits of technology

The external quantum efficiency (PL QY) of perovskite nanorods has been successfully improved from 67% to 85%, and the spectral stability, brightness and external quantum efficiency of light emitting diodes have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823754A_ABST
    Figure CN119823754A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectricity, and relates to a blue-light perovskite nanorod material, a light-emitting diode and a preparation method. The preparation method of the light-emitting diode comprises the following steps: taking lead acetate trihydrate, formamidine acetate, oleylamine bromide and oleic acid as synthetic raw materials, and mixing the materials with a reaction solvent according to a set proportion to obtain a reactant solution system; the method comprises the following steps: at normal temperature, carrying out ultrasonic synthesis on a reactant solution system by using a cell crusher to obtain an FAPbBr3 nanorod original solution, carrying out centrifugal purification on the obtained original solution to obtain an FAPbBr3 nanorod, passivating surface defects of the perovskite nanorod and improving the conductivity of the perovskite nanorod by introducing 4-trifluoromethylbenzene-1-formamidine hydrochloride, and making the perovskite nanorod into a luminescent layer. The defect state density and the non-radiative recombination center of the light-emitting layer are reduced, and the spectral stability is enhanced, so that the brightness and the external quantum efficiency of the device are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optoelectronic technology, and specifically relates to a blue light perovskite nanorod material, a light emitting diode and a preparation method thereof. Background Art

[0002] Halide perovskite nanocrystals are promising materials for light-emitting diodes (LEDs) due to their high photoluminescence quantum yield (PLQY), narrow emission bandwidth, and continuous bandgap tunability. It is well known that the morphology control of nanocrystals has a strong correlation with their optoelectronic properties. One-dimensional nanorods (NRs) have been shown to have higher electronic energy states and surface chemical potentials than spherical nanoparticles due to their lower symmetry, which is beneficial to improve the conductivity, thermal stability, and chemical stability of the material, and is conducive to the exploration of efficient optoelectronic devices.

[0003] However, due to the abundant surface defects of perovskite nanorods, long reaction time and complex synthesis methods, it is still extremely challenging to directly synthesize perovskite nanorods with high PLQY and stability and construct high-performance blue light perovskite LED devices. Summary of the invention

[0004] In view of the shortcomings of the existing blue light perovskite light-emitting diode preparation technology, the purpose of the present invention is to provide a method for preparing a blue light-emitting diode based on perovskite nanorods. The method can conveniently synthesize a perovskite nanorod solution with relatively uniform size using a cell disruptor at a relatively low temperature such as room temperature, and adopt a ligand exchange strategy to reduce the lead ion defects of the perovskite nanorods, while improving the conductivity of the perovskite nanorods, thereby preparing a perovskite light-emitting diode with a stable electroemission spectrum and excellent performance.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted in the first aspect of the present invention is: a method for preparing blue light perovskite nanorods, using lead acetate trihydrate (Pb(Ac)2·3H2O), formamidine acetate (FAAc), oleylamine bromide (OAmBr), and oleic acid (OA) as synthetic raw materials, mixing the synthetic raw materials with a reaction solvent to obtain a reactant solution system; in a cell disruptor, subjecting the reactant solution system to ultrasonic synthesis to obtain a FAPbBr3 nanorod stock solution; purifying the FAPbBr3 nanorod stock solution to obtain FAPbBr3 nanorods; bBr3 nanorods are dispersed in a non-polar solvent to obtain a FAPbBr3 nanorod solution; 4-trifluoromethylbenzene-1-carboxamidine hydrochloride is added to the FAPbBr3 nanorod solution to form a mixed solution, which is stirred for 0.5 to 10 hours, and post-treated to obtain a FAPbBr3 nanorod solution modified with 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC) as a luminescent material solution; a composite substrate is provided, the composite substrate comprising a substrate, an anode, a hole injection layer and a hole transport layer which are stacked in sequence, and the luminescent material solution is coated on the hole transport layer to form a luminescent layer.

[0006] Among them, the mass volume ratio of lead acetate trihydrate, formamidine acetate, oleylamine bromide and oleic acid is (0.01-0.5) g: (0.01-1) g: (0.1-2) g: (1-10) mL; and / or the volume ratio of oleic acid to the reaction solvent is 1: (1-6).

[0007] Wherein, the power of ultrasonic synthesis is 1-90W; and / or, the temperature of ultrasonic synthesis is 0-90°C; and / or, the time of ultrasonic synthesis is 0.5-30min.

[0008] Wherein, in the mixed solution, the volume concentration of 4-trifluoromethylbenzene-1-carboxamidine hydrochloride in the original nanorod solution is 0.01-0.8%.

[0009] The reaction solvent includes one or more of n-octane, toluene, dodecane and octadecene.

[0010] The non-polar solvent includes one or more of toluene, n-hexane and n-octane.

[0011] Among them, the FAPbBr3 nanorod original solution is purified to obtain FAPbBr3 nanorods, including: adding ethyl acetate to the FAPbBr3 nanorod original solution to obtain a first mixed solution system, centrifuging at a centrifugal speed of 2000-12000rpm for 1-30min, removing the supernatant, and taking the precipitate after centrifugation; adding a non-polar solvent to the precipitate to dissolve the precipitate to form a perovskite dispersion, centrifuging at a centrifugal speed of 1000-12000rpm for 1-30min, and taking the supernatant; adding ethyl acetate to the supernatant, mixing evenly, to obtain a second mixed solution system, centrifuging at a centrifugal speed of 2000-12000rpm for 1-30min, removing the supernatant, and taking the precipitate after centrifugation, which is the FAPbBr3 nanorod.

[0012] The second aspect of the present invention provides a light-emitting diode, comprising: a substrate, an anode, a hole injection layer, a hole transport layer and a perovskite light-emitting layer stacked in sequence, wherein the perovskite light-emitting layer comprises FAPbBr3 nanorods, and the surfaces of the FAPbBr3 nanorods are modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride.

[0013] The length of the FAPbBr3 nanorods is 15 to 80 nm, and the width of the nanorods is 3 to 10 nm.

[0014] Among them, the thickness of the perovskite light-emitting layer is 30 to 50 nm;

[0015] The perovskite light-emitting layer further includes an electron transport layer and a cathode on the side away from the hole transport layer.

[0016] The third aspect of the present invention provides a method for preparing a blue light perovskite nanorod material, comprising: using lead acetate trihydrate (Pb(Ac)2·3H2O), formamidine acetate (FAAc), oleylamine bromide (OAmBr), and oleic acid (OA) as synthetic raw materials, mixing the synthetic raw materials with a reaction solvent to obtain a reactant solution system; in a cell disruptor, ultrasonically synthesizing the reactant solution system to obtain a FAPbBr3 nanorod original solution; purifying the FAPbBr3 nanorod original solution to obtain FAPbBr3 nanorods; dispersing the FAPbBr3 nanorods in a non-polar solvent to obtain a FAPbBr3 nanorod solution; adding 4-trifluoromethylbenzene-1-formamidine hydrochloride to the FAPbBr3 nanorod solution to form a mixed solution, stirring for 0.5 to 10 hours, and post-treating to obtain a FAPbBr3 nanorod solution modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride (TFBC).

[0017] The fourth aspect of the present invention includes a blue light perovskite nanorod material, which is prepared by the above-mentioned blue light perovskite nanorod material preparation method. The blue light perovskite nanorod material includes FAPbBr3 nanorods, and the surface of the FAPbBr3 nanorods is modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride.

[0018] In one embodiment of the present invention, the length of the FAPbBr3 nanorods is 15 to 80 nm; the width of the nanorods is 3 to 10 nm 。

[0019] Compared with the prior art, the present invention has the following obvious outstanding substantive features and significant advantages:

[0020] 1) The present invention can conveniently synthesize a FAPbBr3 perovskite nanorod solution with relatively uniform size by using a cell disruptor at room temperature or other relatively low temperatures; by adding 4-trifluoromethylbenzene-1-formamidine hydrochloride ligand when purifying the nanorods, it provides abundant chloride ions that combine with the unsaturated lead ions on the surface of the FAPbBr3 nanorods to reduce the defects on the perovskite surface, and successfully improves the external quantum efficiency (PL QY) from 67% to 85%.

[0021] 2) The 4-trifluoromethylbenzene-1-carboxamidine hydrochloride ligand added in the present invention provides more free π electrons in the aromatic ring than the OA ligand, and can induce the p-doping of FAPbBr3 nanorods and the reduction of trap states in FAPbBr3 nanorods, thereby greatly improving the conductivity of the perovskite nanorod film. The present invention reduces the defect state density and non-radiative recombination center of the light-emitting layer, has strong spectral stability, and significantly improves the brightness and external quantum efficiency of the device.

[0022] 3) The present invention adopts the above-mentioned ligand-exchanged FAPbBr3 nanorod solution to prepare a light-emitting diode with stable spectrum, blue light, external quantum efficiency of 5.86%, and maximum brightness of 2,391 cd m -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a transmission electron microscope image of the perovskite nanorods prepared in Example 2 of the present invention;

[0024] Figure 2 is a time-resolved photoluminescence spectrum of perovskite nanorods prepared in embodiments 1 and 2 of the present invention;

[0025] Figure 3 is an electroluminescence spectrum diagram of the light-emitting diode device prepared in Example 2 of the present invention at different voltages;

[0026] Figure 4is a current density-external quantum efficiency diagram of the light-emitting diode devices prepared in Examples 1 and 2 of the present invention;

[0027] Figure 5 It is a current density-voltage-brightness diagram of the perovskite nanorod light-emitting diode devices prepared in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The terms "first", "second" and "third" in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second" and "third" can explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. All directional indications (such as up, down, left, right, front, back...) in the embodiments of the present invention are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or units inherent to these processes, methods, products or devices.

[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0031] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0032] A first aspect of the present invention provides a method for preparing a light emitting diode, comprising:

[0033] (1) Lead acetate trihydrate (Pb(Ac)2·3H2O), formamidine acetate (FAAc), oleylamine bromide (OAmBr), and oleic acid (OA) are used as synthetic raw materials, and the synthetic raw materials are mixed with a reaction solvent to obtain a reactant solution system; in a cell disruptor, the reactant solution system is subjected to ultrasonic synthesis to obtain a FAPbBr3 nanorod stock solution.

[0034] In the embodiment of the present invention, by controlling the composition of the synthetic raw material, and controlling the addition of the synthetic raw material to the cell crusher for ultrasound, the raw material can be reacted by ultrasound, and the original solution of FAPbBr3 nanorods can be formed. In the embodiment of the present invention, ultrasound is applied in the cell crusher, the power of ultrasound is relatively large, and the time used for ultrasound is relatively short. During the ultrasound process, high-intensity mechanical vibration is generated to generate ultrasonic waves, thereby causing cavitation in the liquid and generating cavities and cavities (bubbles), which grow in the negative pressure area of ​​the sound field and shrink in the positive pressure area of ​​the sound field. The continuous interaction between the bubble and the sound field leads to the growth of the bubble, and finally leads to the violent collapse of the bubble. The implosion of the bubble can generate a high-speed jet and a strong shock wave on the surface of the bulk material, thereby producing a nanomaterial, and making the product of the reaction a nanorod-like structure, and the size of the nanorod-like structure is relatively uniform.

[0035] (2) Purify the original FAPbBr3 nanorod solution to obtain FAPbBr3 nanorods.

[0036] In the embodiment of the present invention, FAPbBr3 nanorods can be purified by centrifugal washing, extraction, etc., and the embodiment of the present invention does not limit the purification method.

[0037] (3) Dispersing FAPbBr3 nanorods in a non-polar solvent to obtain a FAPbBr3 nanorod solution.

[0038] (4) Add 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC) to the FAPbBr3 nanorod solution to form a mixed solution, stir for 0.5 to 10 hours, and post-treat to obtain a 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC)-modified FAPbBr3 nanorod solution as a luminescent material solution.

[0039] In an embodiment of the present invention, TFBC is added to the FAPbBr3 nanorod solution, and 4-trifluoromethylbenzene-1-carboxamidine hydrochloride is used as a ligand, which provides abundant chloride ions to combine with the unsaturated lead ions on the surface of the FAPbBr3 nanorods to reduce the defects on the perovskite surface.

[0040] (5) Providing a composite substrate, the composite substrate comprising a substrate, an anode, a hole injection layer and a hole transport layer stacked in sequence, coating a light-emitting material solution on the hole transport layer to form a light-emitting layer.

[0041] In the embodiment of the present invention, the electron transport layer and the cathode are also prepared after the light emitting layer.

[0042] In an embodiment of the present invention, by ultrasonication in a cell disruptor, at a relatively low temperature such as room temperature, the synthetic raw materials can be controlled to synthesize relatively uniform FAPbBr3 nanorods, so that the morphology uniformity of the luminescent material is better; by adding 4-trifluoromethylbenzene-1-formamidine hydrochloride ligand to the FAPbBr3 nanorod dispersion, it provides abundant chloride ions that combine with the unsaturated lead ions on the surface of the FAPbBr3 nanorods to reduce the defects on the perovskite surface, and successfully improves the PL QY from 67% to 85%; the 4-trifluoromethylbenzene-1-formamidine hydrochloride ligand provides more free π electrons in the aromatic ring than the OA ligand, and can induce p-doping of the FAPbBr3 nanorods and the reduction of trap states in the FAPbBr3 nanorods, thereby greatly improving the conductivity of the perovskite nanorod film. The light-emitting diode prepared from the FAPbBr3 nanorod solution after ligand exchange with 4-trifluoromethylbenzene-1-formamidine hydrochloride has a stable spectrum and emits blue light, with an external quantum efficiency of 5.86% and a maximum brightness of 2,391 cd m -2 .

[0043] In one embodiment of the present invention, the mass volume ratio of lead acetate trihydrate, formamidine acetate, oleylamine bromide and oleic acid is (0.01-0.5) g: (0.01-1) g: (0.1-2) g: (1-10) mL; and / or, the volume ratio of oleic acid to the reaction solvent is 1: (1-6). Among them, the mass volume ratio of lead acetate trihydrate, formamidine acetate, oleylamine bromide and oleic acid can be 0.01 g: 0.01 g: 0.1 g: 1 mL, 0.5 g: 0.01 g: 0.1 g: 1 mL, 0.3 g: 0.01 g: 0.1 g: 1 mL, 0.01 g: 0.08 g: 0.3 g: 5 mL, 0.2 g: 0.06 g: 1 g: 8 mL, 0.4 g: 0.09 g: 1.5 g: 10 mL, etc., or a range value composed of any two of the above values.

[0044] In one embodiment of the present invention, the power of ultrasonic synthesis is 1 to 90W; and / or, the temperature of ultrasonic synthesis is 0 to 90°C; and / or, the time of ultrasonic synthesis is 0.5 to 30min. In an embodiment of the present invention, by controlling the power, temperature and / or time of ultrasound, it is beneficial to have a uniformly sized perovskite nanorod solution. Among them, the power of ultrasonic synthesis can be 1W, 30W, 60W, 70W, 90W, etc., or a range value composed of any two of the above values. The temperature of ultrasonic synthesis can be 0°C, 15°C, 25°C, 35°C, 60°C, 90°C, or a range value composed of any two of the above values. The time of ultrasonic synthesis can be 0.5min, 1min, 3min, 10min, 30min, etc., or a range value composed of any two of the above values.

[0045] In one embodiment of the present invention, in the mixed solution, the volume concentration of 4-trifluoromethylbenzene-1-carboxamidine hydrochloride in the original nanorod solution is 0.01-0.8%. In the mixed solution, the volume concentration of 4-trifluoromethylbenzene-1-carboxamidine hydrochloride in the original nanorod solution can be 0.01%, 0.05%, 0.1%, 0.3%, 0.6%, 0.8%, etc., or a range of any two of the above values.

[0046] In one embodiment of the present invention, the reaction solvent includes one or more of n-octane, toluene, dodecane and octadecene.

[0047] In one embodiment of the present invention, the non-polar solvent includes one or more of toluene, n-hexane and n-octane.

[0048] In one embodiment of the present invention, the FAPbBr3 nanorod original solution is purified to obtain the FAPbBr3 nanorods, comprising: adding ethyl acetate to the FAPbBr3 nanorod original solution to obtain a first mixed solution system, centrifuging at a centrifugal speed of 2000 to 12000 rpm for 1 to 30 minutes, removing the supernatant, and taking the precipitate after centrifugation; preferably, the amount of ethyl acetate added is 10 to 90 mL. A non-polar solvent is added to the precipitate to dissolve the precipitate to form a perovskite dispersion, centrifuging at a centrifugal speed of 1000 to 12000 rpm for 1 to 30 minutes, and taking the supernatant; preferably, the amount of the non-polar solvent added is 1 to 10 mL; preferably, the non-polar solvent includes one or more of toluene, n-hexane and n-octane. Ethyl acetate is added to the supernatant and mixed evenly to obtain a second mixed solution system. The system is centrifuged at a centrifugal speed of 2000 to 12000 rpm for 1 to 30 minutes, and the supernatant is removed. The precipitate after centrifugation is FAPbBr3 nanorods. Preferably, the amount of ethyl acetate added is 1 to 20 mL.

[0049] The second aspect of the present invention provides a light-emitting diode, comprising: a substrate, an anode, a hole injection layer, a hole transport layer and a perovskite light-emitting layer stacked in sequence. In one embodiment of the present invention, the perovskite light-emitting layer comprises FAPbBr3 nanorods, and the surface of the FAPbBr3 nanorods is modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride.

[0050] In the embodiment of the present invention, the light emitting diode has the same advantages as the light emitting diode prepared by the preparation method of the first aspect.

[0051] In one embodiment of the present invention, the length of the FAPbBr3 nanorods is 15 to 80 nm; the width of the nanorods is 3 to 10 nm.

[0052] In one embodiment of the present invention, the thickness of the perovskite light-emitting layer is 30 to 50 nm;

[0053] In one embodiment of the present invention, the perovskite light-emitting layer further includes an electron transport layer and a cathode on a side away from the hole transport layer.

[0054] In one embodiment of the present invention, the anode includes ITO conductive glass, and the thickness of the ITO film is 100-150 nm.

[0055] In one embodiment of the present invention, the hole injection layer includes poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and has a thickness of 20 to 40 nm.

[0056] In one embodiment of the present invention, the hole transport layer comprises poly[bis(4-phenyl)(4-butylphenyl)amine] and has a thickness of 30 to 40 nm.

[0057] In one embodiment of the present invention, the perovskite light-emitting layer includes a nanorod solution, and the thickness thereof is 30 to 50 nm.

[0058] In one embodiment of the present invention, the electron transport layer includes 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene, and the thickness thereof is 30-40 nm.

[0059] In one embodiment of the present invention, the cathode may be modified with LiF having a thickness of 0.1 to 10 nm.

[0060] In one embodiment of the present invention, the cathode comprises Al, and the thickness thereof is 60-300 nm.

[0061] It should be noted that the materials of the above anode, hole injection layer, hole transport layer, electron transport layer and cathode are specific preferred materials provided by the present invention, and the embodiments of the present invention do not limit the specific materials of the anode, hole injection layer, hole transport layer, electron transport layer and cathode.

[0062] The third aspect of the present invention provides a method for preparing a blue light perovskite nanorod material, which is the same as the method for preparing a blue light perovskite nanorod material solution in the light-emitting diode preparation method of the first aspect, and specifically comprises: using lead acetate trihydrate (Pb(Ac)2·3H2O), formamidine acetate (FAAc), oleylamine bromide (OAmBr), and oleic acid (OA) as synthetic raw materials, mixing the synthetic raw materials with a reaction solvent to obtain a reactant solution system; in a cell disruptor, subjecting the reactant solution system to ultrasonic synthesis Obtaining a FAPbBr3 nanorod original solution; purifying the FAPbBr3 nanorod original solution to obtain FAPbBr3 nanorods; dispersing the FAPbBr3 nanorods in a non-polar solvent to obtain a FAPbBr3 nanorod solution; adding 4-trifluoromethylbenzene-1-carboxamidine hydrochloride to the FAPbBr3 nanorod solution to form a mixed solution, stirring for 0.5 to 10 hours, and post-treating to obtain a FAPbBr3 nanorod solution modified with 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC).

[0063] The fourth aspect of the present invention includes a blue light perovskite nanorod material, which is prepared by the above-mentioned blue light perovskite nanorod material preparation method. The blue light perovskite nanorod material includes FAPbBr3 nanorods, and the surface of the FAPbBr3 nanorods is modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride.

[0064] In one embodiment of the present invention, the length of the FAPbBr3 nanorods is 15 to 80 nm; the width of the nanorods is 3 to 10 nm 。

[0065] The above scheme is further described below in conjunction with the accompanying drawings and specific implementation examples. The preferred embodiments of the present invention are described in detail as follows:

[0066] Example 1

[0067] 1. Preparation of blue light perovskite nanorod solution

[0068] a) 0.0570 g of lead acetate trihydrate (Pb(Ac)2·3H2O), 0.0580 g of formamidine acetate (FAAc), 0.2100 g of oleylamine bromide (OAmBr), and 2 mL of oleic acid (OA) as synthetic raw materials are added into a 25 mL beaker containing 8 mL of octane for mixing to obtain a reactant mixed solution system; in a cell disruptor, the reactant solution system is subjected to an ultrasonic synthesis reaction at room temperature at a power of 35 W for 1 min to obtain a nanorod perovskite raw solution; the obtained perovskite nanorods are used as a first precursor.

[0069] b) adding 30 mL of ethyl acetate to the original solution of FAPbBr3 nanorods prepared in step a), mixing them evenly to obtain a mixed solution system, and then centrifuging the mixed liquid at a centrifugal speed of 7000 rpm for 3 minutes to obtain a first precipitate;

[0070] c) adding 2 mL of n-hexane to the first precipitate to dissolve the precipitate to form a perovskite dispersion, which is then centrifuged at 7800 rpm for 1 min, and then the supernatant is taken for further purification;

[0071] d) adding 6 mL of ethyl acetate to the supernatant obtained in step c), mixing uniformly to obtain a mixed solution system, then centrifuging the mixed liquid at a speed of 7000 rpm for 3 min, and removing the supernatant to obtain a second precipitate;

[0072] e) Disperse the second precipitate in 4 mL of n-hexane and adjust the volume to a final concentration of 6 mg mL -1 FAPbBr3 nanorod solution.

[0073] 2. Preparation of Light Emitting Diodes

[0074] a). Cleaning of the ITO conductive glass substrate etched with an anode: Wipe the ITO glass substrate with a dust-free cloth soaked in detergent, then use deionized water, acetone and isopropanol for continuous ultrasonic cleaning for 15 minutes each, dry the glass substrate and use an oxygen plasma cleaner for 15 minutes.

[0075] b). Preparation of hole injection layer: 150 μL poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) aqueous solution was spin-coated onto ITO at a speed of 4000 rpm for 40 s, and then placed on a heating table at 150° C. for annealing in air for 20 min.

[0076] c) Preparation of hole transport layer: Transfer the substrate to a nitrogen-filled glove box (water and oxygen content less than 0.1 ppm), take 120 μL of 8 mg mL -1 A chlorobenzene solution of poly[bis(4-phenyl)(4-butylphenyl)amine] was spin-coated onto the hole injection layer at 4000 rpm for 40 seconds, and then placed on a heating stage at 150° C. for annealing for 20 minutes.

[0077] d). Preparation of perovskite light-emitting layer: Take 100 μL of the nanorod solution prepared in step 1, and spin-coat it onto the hole transport layer at 1500 rpm for 1 min without annealing.

[0078] e) Preparation of electron transport layer: Transfer the substrate to a vacuum coating machine. When the vacuum degree is less than 4×10-4 Pa 1,3,5-Tris(1-phenyl-1H-benzimidazol-2-yl)benzene was deposited at an evaporation rate of 40 nm to a thickness of 40 nm.

[0079] f). Preparation of electrode modification layer: LiF was deposited at an evaporation rate of 1 nm thick.

[0080] Preparation of cathode: The Al electrode was deposited at an evaporation rate of 100 nm in thickness.

[0081] 3. Experimental test analysis

[0082] The device performance test of the light emitting diode of this embodiment was carried out, and the external quantum efficiency-current density curve of the perovskite nanorod LED device was obtained ( Figure 4 ) and the current density-voltage-brightness diagram ( Figure 5 ), it can be seen from the figure that the external quantum efficiency is as high as 3.79%; the maximum brightness reaches 981cd m -2 .

[0083] Example 2

[0084] 1. Preparation of 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC) modified perovskite nanorod solution

[0085] a). 0.0570 g of lead acetate trihydrate (Pb(Ac)2·3H2O), 0.0580 g of formamidine acetate (FAAc), 0.2100 g of oleylamine bromide (OAmBr), and 2 mL of oleic acid (OA) as synthetic raw materials were added into a 25 mL beaker containing 8 mL of octane for mixing to obtain a reactant mixed solution system; in a cell disruptor, the reactant solution system was subjected to an ultrasonic synthesis reaction at room temperature at a power of 35 W for 1 min to obtain a nanorod perovskite raw solution; the obtained perovskite nanorods were used as the first precursor.

[0086] b) adding 30 mL of ethyl acetate to the original solution of FAPbBr3 nanorods prepared in step a), mixing evenly to obtain a mixed solution system, and then centrifuging the mixed liquid at a centrifugal speed of 7000 rpm for 3 min to obtain a first precipitate;

[0087] c) adding 2 mL of n-hexane to the first precipitate to dissolve the precipitate to form a perovskite dispersion, which was then centrifuged at 7800 rpm for 1 min, and then the supernatant was purified again;

[0088] d) adding 6 mL of ethyl acetate to the supernatant obtained in step c), mixing evenly to obtain a mixed solution system, and then centrifuging the mixed liquid at a speed of 7000 rpm for 3 min, removing the supernatant to obtain a second precipitate;

[0089] e) Disperse the second precipitate in 4 mL of n-hexane and adjust the volume to obtain a final concentration of 6 mg mL -1 FAPbBr3 nanorod solution;

[0090] f) Preparation of TFBC-modified perovskite nanorods: Add 40 μL of TFBC to the perovskite nanorod solution obtained in step e) above and stir for 1 hour to perform ligand exchange, then centrifuge the product at a centrifugal speed of 5000 rpm for 1.5 min, then take the supernatant to obtain a perovskite nanorod solution with uniform morphology, and place it in a refrigerator for later use;

[0091] 2. Preparation of Light Emitting Diodes

[0092] g). Cleaning of the ITO conductive glass substrate etched with an anode: Wipe the ITO glass substrate with a dust-free cloth moistened with detergent, then clean it with deionized water, acetone and isopropanol for 15 minutes each by continuous ultrasonic cleaning, dry the glass substrate and clean it with an oxygen plasma cleaner for 15 minutes.

[0093] h). Preparation of hole injection layer: 150 μL poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) aqueous solution was spin-coated onto ITO at a speed of 4000 rpm for 40 s, and then placed on a heating table at 150° C. for annealing in air for 20 min.

[0094] i) Preparation of hole transport layer: Transfer the substrate to a nitrogen-filled glove box (water and oxygen content less than 0.1 ppm), take 120 μL of 8 mg mL -1 A chlorobenzene solution of poly[bis(4-phenyl)(4-butylphenyl)amine] was spin-coated onto the hole injection layer at 4000 rpm for 40 seconds, and then placed on a heating stage at 150° C. for annealing for 20 minutes.

[0095] j). Preparation of perovskite light-emitting layer: Take 100 μL of the nanorod solution prepared in step 1, and spin coat it onto the hole transport layer at 1500 rpm for 1 min. No annealing treatment is required.

[0096] k) Preparation of electron transport layer: Transfer the substrate to a vacuum coating machine. When the vacuum degree is less than 4×10 -4 Pa 1,3,5-Tris(1-phenyl-1H-benzimidazol-2-yl)benzene was deposited at an evaporation rate of 40 nm to a thickness of 40 nm.

[0097] l). Preparation of electrode modification layer: LiF was deposited at an evaporation rate of 1 nm thick.

[0098] m). Preparation of cathode: The Al electrode was deposited at an evaporation rate of 100 nm in thickness.

[0099] 3. Experimental test analysis

[0100] The blue light emitting diode based on the perovskite nanorods modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride of Example 2 was subjected to thin film electrical characterization and device performance testing, and a scanning electron microscope image of the film was obtained ( Figure 1 ), it can be seen from the figure that the FAPbBr3 modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride presents a rod-like structure, the length of the FAPbBr3 nanorods is 15 to 80 nm, and the width of the nanorods is 3 to 10 nm; the time-resolved photoluminescence spectra of the perovskite nanorod films with and without ligand modification ( Figure 2 ), it can be seen from the figure that the average carrier lifetime in the nanorod film modified by TFBC is significantly increased; the electroluminescence spectrum of the perovskite nanorod LED device ( Figure 3 ), external quantum efficiency-current density curve ( Figure 4 ) and the current density-voltage-brightness diagram ( Figure 5 ). The peak of the electroluminescence spectrum of the device is located at 488nm, and the half-peak width is 24nm. Figure 3 As shown; Figure 4 The maximum external quantum efficiency shown is 5.86%, Figure 5 The maximum brightness shown is 2391cd m -2 , which shows that this method is an effective solution for preparing blue light emitting diode devices. Figure 2 , Figure 4 and Figure 5 In the figure, NRs-untreated represents the FAPbBr3 nanorods corresponding to Example 1, and NRs-TFBC represents the TFBC-modified FAPbBr3 nanorods corresponding to Example 2.

[0101] Example 3

[0102] The difference from Example 2 is that the reactant solution system is subjected to ultrasonic synthesis reaction at room temperature for 5 minutes at a power of 90 W in a cell disruptor. The rest is the same as Example 2 and will not be described again.

[0103] Example 4

[0104] The difference from Example 2 is that the reactant solution system is subjected to ultrasonic synthesis reaction at room temperature and 1 W power for 30 minutes in a cell disruptor. The rest is the same as Example 2.

[0105] Example 5

[0106] The difference from Example 2 is that TFBC is added and stirred for 10 hours, and the volume concentration of TFBC is 0.8% to allow ligand exchange. The rest is the same as Example 2.

[0107] Example 6

[0108] The difference from Example 2 is that TFBC is added and stirred for 0.5 h, and the volume concentration of TFBC is 0.06% to allow ligand exchange. The rest is the same as Example 2.

[0109] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a light emitting diode, characterized in that: The following steps are involved: (1) using lead acetate trihydrate, formamidine acetate, oleylamine bromide, and oleic acid as synthetic raw materials, mixing the synthetic raw materials with a reaction solvent to obtain a reactant solution system; subjecting the reactant solution system to ultrasonic synthesis in a cell disruptor to obtain a FAPbBr3 nanorod stock solution; (2) purifying the FAPbBr3 nanorod original solution to obtain FAPbBr3 nanorods; (3) dispersing the FAPbBr3 nanorods in a non-polar solvent to obtain a FAPbBr3 nanorod solution; (4) adding 4-trifluoromethylbenzene-1-formamidine hydrochloride to the FAPbBr3 nanorod solution to form a mixed solution, stirring for 0.5 to 10 hours, and post-treating to obtain a 4-trifluoromethylbenzene-1-formamidine hydrochloride-modified FAPbBr3 nanorod solution as a luminescent material solution; (5) Providing a composite substrate, the composite substrate comprising a substrate, an anode, a hole injection layer and a hole transport layer stacked in sequence, and coating the luminescent material solution on the hole transport layer to form a luminescent layer.

2. The method for preparing a light emitting diode according to claim 1, characterized in that: The mass volume ratio of lead acetate trihydrate, formamidine acetate, oleylamine bromide and oleic acid is (0.01-0.5) g: (0.01-1) g: (0.1~2)g: (1~10)mL; and / or, The volume ratio of the oleic acid to the reaction solvent is 1:(1-6).

3. The method for preparing a light emitting diode according to claim 1, characterized in that: The power of the ultrasonic synthesis is 1 to 90 W; and / or, The temperature of the ultrasonic synthesis is 0 to 90° C.; and / or, The ultrasonic synthesis time is 0.5 to 30 minutes.

4. The method for preparing a light emitting diode according to any one of claims 1 to 4, characterized in that: In the mixed solution, the volume concentration of the 4-trifluoromethylbenzene-1-carboxamidine hydrochloride in the original nanorod solution is 0.01-0.8%.

5. The method for preparing a light emitting diode according to claim 1, characterized in that: The reaction solvent includes one or more of n-octane, toluene, dodecane and octadecene; and / or The non-polar solvent includes two or more of toluene, n-hexane and n-octane.

6. The method for preparing a light emitting diode according to claim 1, characterized in that: The method of purifying the FAPbBr3 nanorod original solution to obtain FAPbBr3 nanorods comprises: Adding ethyl acetate to the original FAPbBr3 nanorod solution to obtain a first mixed solution system, centrifuging at a centrifugal speed of 2000 to 12000 rpm for 1 to 30 minutes, removing the supernatant, and taking the precipitate after the centrifugal treatment; Adding a non-polar solvent to the precipitated material to dissolve the precipitated material to form a perovskite dispersion, centrifuging at a centrifugal speed of 1000 to 12000 rpm for 1 to 30 minutes, and taking a supernatant; Ethyl acetate is added to the supernatant and mixed evenly to obtain a second mixed solution system. The system is centrifuged at a centrifugal speed of 2000 to 12000 rpm for 1 to 30 minutes, the supernatant is removed, and the precipitate after the centrifugal treatment is the FAPbBr3 nanorods.

7. A light emitting diode, characterized in that: include: A substrate, an anode, a hole injection layer, a hole transport layer and a perovskite light-emitting layer are stacked in sequence, wherein the perovskite light-emitting layer comprises FAPbBr3 nanorods, and the surfaces of the FAPbBr3 nanorods are modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride.

8. The method for preparing a light emitting diode according to claim 7, characterized in that: The length of the FAPbBr3 nanorod is 15-80 nm; the width of the nanorod is 3-10 nm; Preferably, the thickness of the perovskite light-emitting layer is 30 to 50 nm; Preferably, the perovskite light-emitting layer further includes an electron transport layer and a blue light cathode on a side away from the hole transport layer.

9. A method for preparing a blue light perovskite nanorod material, characterized in that: include: Lead acetate trihydrate (Pb(Ac)2·3H2O), formamidine acetate (FAAc), oleylamine bromide (OAmBr), and oleic acid (OA) are used as synthetic raw materials, and the synthetic raw materials are mixed with a reaction solvent to obtain a reactant solution system; in a cell disruptor, the reactant solution system is subjected to ultrasonic synthesis to obtain a FAPbBr3 nanorod original solution; Purifying the FAPbBr3 nanorod original solution to obtain FAPbBr3 nanorods; dispersing the FAPbBr3 nanorods in a non-polar solvent to obtain a FAPbBr3 nanorod solution; The FAPbBr3 nanorod solution is added with 4-trifluoromethylbenzene-1-carboxamidine hydrochloride to form a mixed solution, which is stirred for 0.5 to 10 hours and post-treated to obtain a FAPbBr3 nanorod solution modified with 4-trifluoromethylbenzene-1-carboxamidine hydrochloride (TFBC).

10. A blue light perovskite nanorod material, characterized in that: Prepared by the preparation method of claim 9, the blue light perovskite nanorod material comprises FAPbBr3 nanorods, and the surface of the FAPbBr3 nanorods is modified with 4-trifluoromethylbenzene-1-formamidine hydrochloride; Preferably, the length of the FAPbBr3 nanorod is 15 to 80 nm; the width of the nanorod is 3 to 10 nm. 。